A Review of Survey Instruments and Pharmacy Student Outcomes for Stress, Burnout, Depression and Anxiety - Kelly C. Lee; Austin Yan; Tram B. Cat; Shareen Y. El-Ibiary (MDPI AG, 2024)
While the need to measure burnout, stress and mental health among pharmacy students has been emphasized in the literature, there is limited information on which validated scales should be used. The objective of this scoping review was to identify published studies that used validated scales for burnout, stress and mental health among pharmacy students to provide recommendations for implementation at schools/colleges of pharmacy. Thirty-two out of 153 articles published in the United States from 1 January 2000 to 30 September 2022 were included and categorized into studies measuring stress (20), burnout (4) and depression/anxiety (8). The most common validated scales used to assess stress and burnout among pharmacy students were the Perceived Stress Scale (PSS) and the Maslach Burnout Inventory and the Oldenburg Burnout Inventory, respectively. For mental health, anxiety was most commonly investigated using a variety of scales such as the Generalized Anxiety Disorder-7; the Patient Health Questionnaire, 9-item was used to measure depression in two studies. Validity, ease of use, cost and generalizability are important considerations for selecting a scale. The PSS has been studied extensively in pharmacy students and has been correlated with other well-being domains. Studies that measured burnout and mental health (specifically, depression and anxiety) have less published evidence among pharmacy students.